Implikasi Kehilangan atau Perubahan Kewarganegaraan terhadap Keabsahan Perwakilan - Serlina AtaillaWidya Fatimah; Rosyid Nur Huda; Nafisatul Laila (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This research seeks to examine how changes in citizenship influence the legal validity of marriage, emphasizing both juridical aspects and practical implications. In an era of globalization and increased international mobility, the phenomenon of changing or losing citizenship has become more frequent. The legal consequences of such changes for marital validity represent a crucial area that demands comprehensive analysis, particularly in relation to national and international marriage laws. The study combines an international literature review with empirical data and legal analysis derived from the works of Mr. Mustain, a lecturer at UIN Raden Mas Said Surakarta. Findings reveal that a shift in citizenship can alter the legal standing of a marriage, generate legal ambiguities, and influence family rights such as child custody and inheritance. To address these issues, regulatory harmonization, the proactive engagement of religious authorities, and legal reform at the national level are essential to ensure adequate legal protection for couples undergoing citizenship transitions. Employing a library research method with a qualitative-normative approach, this study analyzes statutory provisions, judicial rulings, and relevant scholarly sources. The findings underscore that citizenship alteration may impact the legality of marriage, particularly when legal systems differ between the country of origin and the newly acquired nationality. In summary, citizenship changes can lead to legal uncertainty regarding marital validity, underscoring the need for legal harmonization and clear protective frameworks for affected couples. This research thus contributes significantly to the discourse on marriage law and citizenship policy development.